Excellent Polyimide Dielectrics Containing Conjugated ACAT for High‐Temperature Polymer Film Capacitor. Issue 11 (12th September 2021) - Wu, Zhiqiang; Guo, Qiang; Liu, Yang; Zhou, Huihui; Zheng, Hua; Lei, Xingfeng; Gong, Lei; Chen, Yanhui; Liu, Zhenguo; Zhang, Qiuyu
Abstract: In order to meet the requirements of polymer dielectric materials for high thermal stability and excellent dielectric properties in the application of high‐temperature film capacitors, a series of polyimide (PI) films are fabricated by introducing a self‐synthesized aniline trimer (ACAT) with a conjugated structure in this work. Since the conjugated ACAT in the main chains of PI improves the electron polarization and carrier mobility of the PI molecular chains, the dielectric constant of the ACAT‐PI films is greatly enhanced (4.4–7.4). Meanwhile, the dissipation factor does not increase apparently (0.002–0.013). The dielectric properties are stable even when the temperature is up to 200 °C, the thermal degradation temperature is as high as 450 °C, and the mechanical properties are also excellent (70–105 MPa). Among all the films, the PI film with 5 mol% ACAT exhibits the maximal energy density of 3.6 J cm −3 under the field of 426 kV mm −1, the high tensile strength (90 MPa) and the excellent thermal stability ( T d5 = 515 °C). The work paves the way to prepare high‐temperature polymer dielectric film materials with high energy storage density. Abstract : A series of polyimide films are fabricated by introducing self‐synthesized aniline trimer (ACAT) with conjugated structure. ACAT‐PI films show excellent dielectric properties and thermal stability. The PI film with 5 mol% ACAT exhibits the maximal energy density of 3.6 J cm −3 under the field of 426 kV mm −1 . The work paves the way to prepare high‐temperature polymer dielectric film materials.